Association Between Covid-19 Knowledge and Anxiety Among Late-Term Pregnant Women - Paramita, Noviana Jihan; Astuti, Sri Lestari Dwi; Handayani, Siti (Interest : Jurnal Ilmu Kesehatan, 2023)
Background: Pregnant women are vulnerable to infections, including Covid-19, and the lack of effective health services can contribute to psychological distress, particularly anxiety. This anxiety is often due to misinformation and insufficient knowledge about Covid-19 prevention. To examine the relationship between Covid-19 prevention knowledge and anxiety levels in pregnant women during the 3rd trimester. Method: This correlational study used a cross-sectional design. A total of 43 pregnant women were selected using total sampling. Data were collected using the Covid-19 knowledge questionnaire and the modified Perinatal Anxiety Screening Scale, specifically designed for the Covid-19 pandemic. Results: A significant relationship was found between Covid-19 prevention knowledge and anxiety levels in the 3rd trimester (p-value = 0.017). Conclusion: Higher knowledge of Covid-19 prevention is associated with lower anxiety levels in pregnant women during the 3rd trimester. Nurses play a key role in providing accurate information to reduce anxiety.